[PP.11.12] VASCULAR ABNORMALITIES AS PREDOMINANT FEATURE IN ALAGILLE SYNDROME PATIENTS WITH A NOVEL MUTATION IN JAG1 GENE. (September 2016) - Santamaria, R.; Lopez-Aguilera, J.; De Caldas, R.Gonzalez; Sanchez-Frias, M.; Garcia-Rios, A.; Buendia, P.; Aljama, P.
Abstract : Objective: Anomalies of aorta and major branches are often related with hereditary diseases affecting vasculogenesis. These are complex conditions with awkward diagnosis and usually fatal consequences. Alagille Syndrome (AS) is a hereditary disorder altering Notch signalling pathway (major role in angiogenesis). Intrahepatic cholestasis (IC) and paucity of intrahepatic bile ducts (PIBD) are main features, occasionally accompanied by major vessels abnormalities (VA). Better clinical descriptions and pathophysiologic understanding of this entity are necessary to improve the prognosis. Objectives: 1. To characterize VA in a case series of AS patients with novel JAG1 mutation. 2. To describe the effects of an antioxidant agent on vascular function and inflammatory markers in a patient with AS. Design and method: Descriptive study of a family with 5 members with clinical diagnosis of AS and a novel mutation in JAG1. Results: Summary of cases: Case #1 (C1). 21 years-old female presenting hypertensive encephalopathy and refractory hypertension (RH). Previous diagnosis: patent ductus arteriosus, coarctation of the thoracic aorta, hypoplasia of abdominal aorta (HAA) and right renal artery estenosis (RRAE). No IC. Case #2 - (Brother of C1). 24 years-old male. RH, HAA and RRAE. No IC. Case #3 - (Brother of C1). 13 years-old male. IC with PIBD. Deceased (massive subarachnoid hemorrhage). Case #4 - (Sister of C1). 15 years-old female. IC, PIBD and mild pulmonary stenosis. Case #5 - (Son of C2). 3 years-old male. IC and PIBD. Case #6 (father of C1, 2, 3 and 4). Sudden death at 42 years-old. Case #7 (mother of C1, 2, 3 and 4). No vascular or liver disease. A heterozygous novel mutation in JAG1 (c.767 G> T; p.Gly256Val) has been found in cases #1, #2, #4 and #5, compatible with the clinical diagnosis of AS. For the first time in AS, a serendipitous observation that inflammatory markers (ferritin, c-reactive protein and albumin) and endothelial function were improved with oral N-acetylcysteine is also described. Conclusions: 1. AS must be considered in patients with unexplained vascular abnormalities. 2. Oxidative stress and inflammation might play a crucial role in the progression of vascular injury in AS.